FRIB Cryogenic Plant Status. Issue 1 (November 2015) - Dixon, K; Ganni, V; Knudsen, P; Casagrande, F
Abstract: After practical changes were approved to the initial conceptual design of the cryogenic system for MSU FRIB and an agreement was made with JLab in 2012 to lead the design effort of the cryogenic plant, many activities are in place leading toward a cool-down of the linacs prior to 2018. This is mostly due to using similar equipment used at CHLII for the 12 GeV upgrade at JLab and an aggressive schedule maintained by the MSU Conventional Facilities department. Reported here is an updated status of the cryogenic plant, including the equipment procurement status, plant layout, facility equipment and project schedule.